Studi Analisis Karakter Gaya Hidup Pendidikan Mahasiswa di Perguruan Tinggi - Indari; ST. Fatimah; Dalilah (Jurnal Bina Ilmu Cendekia, 2024)
The problem of reality that occurs in a group of students who are studying at a State University. Students have different characters due to the environment around them. Environmental factors such as student habits in coffee shops. Starbucks Coffee which is one of the coffee shops that provides expensive prices only for drinks or snacks, not only that, Starbucks is also identical to a group of exclusive people, especially high-class executives. But a group of students who also consume drinks or snacks at Starbucks Coffee. If you see it yourself at Starbucks Coffee, it is not so obvious that there is a group of students at Starbucks. Therefore, the problem of research on the lifestyle of students when they are at Starbucks Coffee. Qualitative research methods with an interpretive paradigm that specifically uses his main theory from Thorstein Veblen about the leisure class and his supporting theory about the consumer society from Jean Baudrillard. In this writing, the social reasons for following a relaxed lifestyle as done by the leisure class at Starbucks Coffee began with an invitation from his friends, until they admitted that it had become a daily activity that had to be done. So that a group of students gave a statement that the taste given was very good and the atmosphere was very comfortable. For economic reasons, students with the pocket money they get are enough to buy drinks and snacks even though they also admit that the prices given are expensive and not comparable. Therefore, these students enjoy their relaxed lifestyle and the emergence of high consumption. The relaxed lifestyle that occurs in the group of students who enjoy Starbucks coffee is the same as the leisure class. Because it is still unclear what group of students with what criteria to be included in the group of students who enjoy a relaxed lifestyle at Starbucks.